Silent voice: harnessing deep learning for lip-reading in Bangla - Shaheen, Munia; Ifti, Akib Zabed; Hassan, Ariful; Hossain, Junaed (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2024.